Køn i cyberspace - Markussen, Randi (Kvinder, Køn & Forskning, 1998)
The article suggests that questions of sex/gender and advanced information technologies can be addressed through the concept it encircles prevaling discourses about sex/gender and technology and analyses the mertaphor of cyberspece within the context of a genealogical approach to the history of information. Furthermore Donna Haraway’s cyborg metaphor introduses as an instance of feminist metaphorical work and the article seeks from prevailing discourses about technology. Finally it shortly decodes the rhetoric of the Danish information society report enlightened by a ’sense of cyborg’.